Characterization of Banana Peel Waste Fermented by Lactobacillus casei and Its Antibacterial Potential - Hidayat, Habibi; Muhammad Ilham Linsukma; Romadhonsyah, Fitra; Purwaningsih, Tuti (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
Humans need energy for various activities, especially economic, household, industrial, business and transportation activities. Most of the world's energy supply comes from fossil fuels which are non-renewable resources. World energy needs are expected to continue to increase, while oil and coal reserves are increasingly depleting. The calculation number of colonies carried out, it was obtained that it was 13,107 CFU/mL. The number of colonies produced shows that there are a large number of lactic acid bacteria present in the sample to produce a certain amount of electrical energy. Macroscopic observation the shape was round, irregular, yellowish white, convex, bacillus form with Gram positive bacteria. The pH tolerance of bacteria when compared with controls, includes pH 4 (not cloudy); 6 (cloudy); 7 (cloudy); 8 (less cloudy) and 10 (less cloudy). The larger the clear zone, the more effective the antibacterial is against certain bacteria. S. typhi has a clear zone of approximately 12 mm, indicating a high level of antibacterial activity against this bacterium. S. epidermidis: The clear zone decreases to about 10 mm, which means its antibacterial activity is lower than that of S. typhi. Meanwhile, K. pneumoniae, S. pyogenes: Both have almost the same clear zone at around 10 mm, which indicates moderate antibacterial activity. S. aureus showed a slight increase in the clear zone around 11 mm, indicating relatively stronger activity against the E. coli had a clear zone of about 10 mm, indicating that the sample had similar antibacterial effects to K. pneumoniae and S. epidermidis. Variation in antibacterial effectiveness of samples against different types of bacteria. This sample is most effective against S. typhi and less effective against S. epidermidis and E. coli. The redox reaction that occurs at each (Zn/Pb; Zn/Cu; Pb/Cu) electrode produces an average voltage for 60 minutes with a measurement variation every 5 minutes of (0.4; 0.8; 0.2 mV). At a wavelength of 3326.67 cm-1 the peak around this area usually indicates the presence of a hydroxyl group (-OH), such as in alcohols or carboxylic acids. It can also indicate amine groups (-NH) on proteins or nitrogen-containing polymers typically found in flavonoids, alkaloids, or phenolic compounds. -OH groups are generally found in compounds with antioxidant activity, such as flavonoids and phenols.